Devops:A Culture, Not A Technology Continuous Integration for Digital Enterprises - Misba, Syeda; Biradar, Shilpa (International Journal of Computer Sciences and Engineering, 2019)
Devops is a collaboration of development and operation devised to stress on communication and integration between them. It is supported by a culture collaboration it helps an organization to grow with these help organization can produce software products and services. Organization associated themselves with devops to startup new methodology. Continuous development and innovation are required in an organization so devops training has been started in the orientation. Companies are focusing on the automation of the process this way timely deliver and quality results are achieved We also found that DevOps is supported by a culture of collaboration, automation, measurement, information sharing and web service usage. DevOps benefits IS development and operations performance. It also has positive effects on web service development and quality assurance performance. Finally, our mapping study suggests that more research is needed to quantify these effects.